Education-occupation mismatch of migrants in the Italian labour market: the effect of social networks - Pierre Georges Van Wolleghem; Marina De Angelis; Sergio Scicchitano (Global Labor Organization (GLO), 2019)
Whilst migration has become a structural feature of most European countries, the integration of foreigners in the labour market continues to raise concerns. Evidence across countries shows that migrants are more often over-educated than natives. Over the last years, scholarship has intended to capture the effect of informal networks on migrants' over-education. Interestingly, no study has looked into the Italian case, yet a country for which the effect of networks on education-occupation mismatch is well documented. This article has two objectives: it assesses the extent to which over-education affects migrants and it evaluates the role informal networks play in producing it. We find that foreigners are more over-educated than natives but that the role of networks is consistent across the two groups. Empirical evidence is drawn from the application of quantitative and counter-factual methods to PLUS 2018 – Participation, Labour, Unemployment Survey.
Keywords: F22; J61; Z13; 330; Network; Over-education; Migrants; labour market